PENGARUH CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar Di Bursa Efek Indonesia) - Ayu Novianti; Fenny Marietza (JURNAL FAIRNESS, 2022)
This study aims to examine the effect of corporate governance on earnings management. The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2017 period. The sample is determined based on the philosophy of portisivism, so that a sample of 82 companies was obtained with a total of 306 observations. Data analysis techniques using multiple linear regression analysis with earnings management as the dependent variable, corporate governance as an independent variable. Processing data using SPSS version 22.0 for Windows. The results show that corporate governance has a negative effect on earnings management For the next researcher in order to expand or add research samples to the financial company sector or all companies listed on the Indonesian stock exchange and add to the period of research observation